2017
DOI: 10.3389/fnbeh.2017.00030
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Neonatal Exposure to Low Frequency Noise Based on Balance in Mice

Abstract: General electric devices and ventilation systems are known to generate low frequency noise (LFN) with frequencies of <100 Hz. Previous studies showed that exposure to LFN caused impairments of balance in humans and mice during adulthood. On the other hand, a previous study showed that noise levels in the neonatal intensive care unit (NICU) were greater than those in general home or office environments. Therefore, it is possible that neonates have a potential risk to be exposed to LFN in the NICU. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…This is quite problematic since many studies affirm that most of the time, there are elevated low frequency intensities in NICUs (3, 32) caused by electronic devices (46). Although the information is limited, some studies suggest that low frequency exposure may have negative effects on neonates, as is the case for animals with auditory thresholds higher than those of humans (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is quite problematic since many studies affirm that most of the time, there are elevated low frequency intensities in NICUs (3, 32) caused by electronic devices (46). Although the information is limited, some studies suggest that low frequency exposure may have negative effects on neonates, as is the case for animals with auditory thresholds higher than those of humans (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited information on the specific effects caused by the low frequencies to which neonates are exposed. In that regard, a recent study suggested that if low frequency exposures have negative impacts on the health of exposed mice, which have a higher threshold for low frequencies than that for humans [375 (34) and 20 Hz, respectively], they could also have negative impacts on humans (35). Results show that the exposure of mice to low frequency noise with levels of 70 dB over 4 weeks causes permanent imbalance and a reduction of the number of calbindin-positive hair cells in the saccule and utricle (35).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that galvanic vestibular stimulation (GVS) delivered as imperceptible white noise only at an intensity of 270 mA for healthy subjects or 450 mA for patients with bilateral vestibular dysfunction resulted in improvement of balance 28 . Our experimental studies have shown that constitutive exposure to sound with a peak of 100 Hz, 70 dB for 1 month caused impairment of the vestibule in mice 29 , 30 . Therefore, it is possible that the target organ for the sound component at 100 Hz in music is the vestibule.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, the rotarod test score was correlated with the amplitude of cVEMP but not with the latency of cVEMP in this study. The rotarod test has been used for determination of vestibular function [17, 19] and also other physiological functions including motor skill learning [4042]. Therefore, it is unlikely that cVEMP latency is associated with physiological functions other than the vestibular systems.…”
Section: Discussionmentioning
confidence: 99%
“…The method reported previously was used for the rotarod test [19]. Mice (4 weeks of age) were placed on a stable rod of 5.7 cm in diameter (47600-Mouse Rota-Rod, UGO BASILE, Italy), and then the rod was rotated at a constant speed of 10 rpm/min for 10–20 s as training.…”
Section: Methodsmentioning
confidence: 99%